1989
DOI: 10.1007/bf00047341
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigen: Function in metastasis by human colorectal carcinoma

Abstract: Carcinoembryonic antigen (CEA) is a glycoprotein that has been useful as a tumor marker to predict recurrence in gastrointestinal malignancies, but whose biological function has not been elucidated. With the recent evidence that CEA is a member of the immunoglobulin supergene family, CEA may be involved in intercellular recognition and binding. This review examines the role that CEA plays in the development of metastases by colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(25 citation statements)
references
References 82 publications
1
23
1
Order By: Relevance
“…Multiple sequential steps are required to enable a malignant cell to establish metastases at a distant site (23). As the first step, a tumor cell must be released from the primary tumor by loss of cell-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple sequential steps are required to enable a malignant cell to establish metastases at a distant site (23). As the first step, a tumor cell must be released from the primary tumor by loss of cell-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Also, CEA has been implicated in the development of hepatic metastases from colorectal cancers (23,28). It has been shown that poorly metastatic human colon cancer cell lines become highly metastatic when transfected with the cDNA coding for CEA by a mechanism not yet fully understood (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Armitage et al [9] found the highest levels of CEA in patients with well differen tiated tumors, whereas other studies [10,11] have reported that moderately differentiated tumors were associated with higher serum CEA levels than both well and poorly differentiated tumors. It has also been reported that CEA has a direct or indirect role in the metastatic process of colorectal tumors [12], Jessup and Thomas [13] have shown a correlation between circulating CEA levels in pa tients and the ability of the tumor to metastasize to the liver. In our study, Mp tumors were more frequently asso ciated with higher serum levels of CEA and this might be related to the higher malignant potential and higher inci dence of liver métastasés observed in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The structural similarity of cea to intercellular adhesion molecule 1 might alter cell adhesion, which might in turn have a role in cancer invasion and metastasis. Thus, cea might play a role in the metastatic process [31][32][33][34] . Evidence for the role of cea in cancer dissemination was revealed in a study by Hostetter et al 35 , who showed that the rate of liver metastasis in mice transplanted with colorectal tumours increased to 48% from 2% after cea injection.…”
Section: Levels Of Carcinoembryonic Antigen (Cea) and Carbohydrate Anmentioning
confidence: 99%